Mechasonic iris project consisting of a smart lens and smart stick for visually impaired people by using arduino uno and an eco-friendly lithium polymer battery / Muhammad Isyraq Husaini Muliadi ... [et al.] - Husaini Muliadi, Muhammad Isyraq; Nik Saleh, Nik Salida Suhaila; Mohd Yazi, Farhani Nabiha; Nur Sharif, Syaza (Universiti Teknologi MARA, Kedah, 2023)
In the making of the Mechasonic Iris Project, we attempt to address matters that visually impaired people frequently struggle with. This is as such, matters which have been overlooked such as thin obstacles which could be missed by walking sticks. For instance, high signboards within a human’s average height are out of the range that could be detected by walking sticks, visually impaired people had to depend heavily on their memories of every placement of things such as house appliances as those things are not easily accessible by walking sticks and most of them need to be accompanied by their relatives and friends to guide them whenever they are outside as many unforeseen obstructions may occur. Therefore, Mechasonic Iris Project aims to support the visually impaired people which complements the use of a traditional stick. This project inspires to boost the user’s confidence with every step, allowing them to be more independent and to be able to provide the chance for these people to move around with ease wherever they want to go. The main features consist of an ultrasonic sensor, buzzer, Arduino UNO, and rechargeable battery which is Lithium Polymer Battery. This project mechanically works started with, the ultrasonic sensor with the ability to detect obstacles in front and upfront of consumers within 2 meters range and transfer the input to Arduino UNO for coding which is later on, transmitted to the buzzer to ring and vibrate. Hence, we are positive that the commercialization of our product is highly efficient to make sure the inclusiveness of stakeholders in society, an affordable device for all and we are proud to say that the battery used for this project is free of harmful metals such as cadmium, lead, and mercury which makes it environmental friendly which it is not only consumerfriendly but also eco-friendly.